ANALISIS TINGKAT PENDIDIKAN SEBAGAI POTENSI SUMBER DAYA MANUSIA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA COGREG KECAMATAN PARUNG KABUPATEN BOGOR JAWA BARAT - Yan Fauzi; Rahmat Subur (Journal of Research and Publication Innovation, 2025)
This study aims to determine the level of education as a potential human resource in improving the community's economy in Cogreg Village, Parung District, Bogor Regency. This research method uses a descriptive - qualitative method. SWOT analysis was used by considering opinions obtained through direct interviews from government respondents, teachers, and the community. A group discussion (FGD) was then conducted with the Village Head, Village Secretary, and Village Administration Section Head. The results and discussion of this research show several aspects of strengths and opportunities that can be utilized. The results show that Cogreg Village has considerable human resource potential, however, the lack of awareness and development in the field of education raises several problems, including: low levels of community awareness about the importance of education, difficulties in accessing schools from home, and inadequate school facilities. In this study, it was found that the right strategy is to implement the Strenght - Opportunity (SO) Strategy, namely the development of high-quality education programs. This strategy utilizes the advantages of competent educators to design attractive and quality programs. Thus, it is expected to increase student motivation, increase participation, and involve parents more actively in the education process. and Weakness - Opportunity (WO) strategies, namely increasing access to education. This step aims to overcome limitations in education access and infrastructure by utilizing existing opportunities, such as the development of education technology and distance learning. In this way, it is expected that students can more easily access education despite transportation constraints.